The Role of Managerial Support and Peer Networks in the Effectiveness of Digital Team Coaching in Hybrid Work Environments - Ratu Aghnia Raffaidy Wiguna; Ika Swasti Putri; Nur Rizki Wijaya; Rika Nur Widiastutik (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines how managerial support and peer networks enhance digital team coaching effectiveness in Indonesian hybrid work environments. Using quantitative cross-sectional survey, data from 130 employees and managers in technology, finance, transportation, entrepreneur and education sectors were analyzed via SPSS to assess correlation and regression effects among managerial support, peer networks, and team performance. Findings highlight the critical role of leadership engangement and peer collaboration in optimizing digital coaching outcomes, providing actionable strategies for organizattions to strengthen hybrid team dynamics. The study underscores the need for structured support systems to bridge mplementation gaps in resource constrained settings.